2020
DOI: 10.24110/0031-403x-2020-99-6-119-126
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children Associated With New Coronavirus Infection (Covid-19): Clinical and Morphological Comparisons

Abstract: Multisystem Inflammatory Syndrome in Children (MIS-C) associated with new coronavirus infection (COVID-19), with signs of Kawasaki disease (KD) and toxic shock syndrome, well-defined diagnostic criteria, is the most severe manifestation of COVID-19 in pediatric patients. MIS-C is analogous to the cytokine storm in children with COVID-19. The article presents a clinical observation of a child with MIS-C with a lethal outcome. Clinical and anamnestic data, the results of laboratory and instrumental research allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Another publication describes pathomorphological signs of myocarditis (with cellular infiltration and necrosis of cardiomyocytes) and coronaritis in the 2-year-old child with IgM and IgG antibodies to SARS-CoV-2 who died of MIS-C 4 weeks after family contact. In this case, the autopsy revealed histopathological signs of the hemophagocytic syndrome ( 41 ).…”
Section: Discussionmentioning
confidence: 75%
“…Another publication describes pathomorphological signs of myocarditis (with cellular infiltration and necrosis of cardiomyocytes) and coronaritis in the 2-year-old child with IgM and IgG antibodies to SARS-CoV-2 who died of MIS-C 4 weeks after family contact. In this case, the autopsy revealed histopathological signs of the hemophagocytic syndrome ( 41 ).…”
Section: Discussionmentioning
confidence: 75%
“…There have been a few case reports on the histology of myocarditis in MIS-C patients; however, there have not been any reports about pericarditis in such patients. 10,11 CD8 + T cell infiltration has been predominant in adult COVID-19-associated pericarditis. 12 We observed various inflammatory cell infiltration, including CD8 + or CD4 + T cells, macrophages and granulocytes but not CD20 + B cells, in the pericardium of a child with MIS-C, although SARS-CoV-2 could not be detected in the pericardial tissue by RT-PCR or immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in MIS‐C the number of inflammatory cells and inflammatory cytokine production were increased in the peripheral blood; 9 however, few findings from tissue specimens have been reported. There have been a few case reports on the histology of myocarditis in MIS‐C patients; however, there have not been any reports about pericarditis in such patients 10,11 . CD8 + T cell infiltration has been predominant in adult COVID‐19‐associated pericarditis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…В период с 17 мая 2020 г. по 22 июня 2021 г. в МДГКБ были госпитализированы 214 детей с детским мультисистемным воспалительным синдромом, ассоциированным с COVID-19. Эффективность терапии, включая применение экстракорпоральной мембранной оксигенации, была достигнута у 213 больных, у одной из первых пациенток заболевание закончилось летальным исходом [56][57][58]. Сотрудники больницы явились авторами клинических рекомендаций по COVID-19 у детей [59].…”
unclassified